The Influence of e-Promotion, Trust, Convenience, and e-WOM on Purchase Decision with Consumer Behavior as a Mediator - Prastowo, Sugeng Lubar; Nur, Muhammad (PERFECT EDUCATION FAIRY, 2023)
This research examines the influence of e-Promotion, consumer trust, convenience, and e-WOM on the purchase decisions of Shopee consumers, with consumer behavior as a mediating variable. The research methodology employed a quantitative approach, utilizing non-probability purposive sampling with a sample size of 494 respondents. Data analysis was conducted using descriptive and inferential statistics, employing the Smart PLS 3.0 software. The research findings demonstrate that trust, convenience, and e-WOM have a significant direct impact on consumer behavior, whereas e-Promotion does not directly affect consumer behavior. The variables e-Promotion, trust, convenience, and Shopee consumer behavior have a direct and significant influence on purchase decisions, while e-WOM does not directly affect the purchase decisions of Shopee customers. Trust, convenience, and e-WOM have a significant indirect impact on purchase decisions with consumer behavior as a mediating variable, whereas e-Promotion does not have an indirect impact on purchase decisions with consumer behavior as a mediating variable.